2023
DOI: 10.1002/jcv2.12186
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal studies of child mental disorders in the general population: A systematic review of study characteristics

Theodora Bogdan,
Weiyi Xie,
Habeba Talaat
et al.

Abstract: IntroductionLongitudinal studies of child mental disorders in the general population (herein study) investigate trends in prevalence, incidence, risk/protective factors, and sequelae for disorders. They are time and resource intensive but offer life‐course perspectives and examination of causal mechanisms. Comprehensive syntheses of the methods of existing studies will provide an understanding of studies conducted to date, inventory studies, and inform the planning of new longitudinal studies.MethodsA systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…Participants achieved an 87% completion rate of the entire research protocol, surpassing the expected rate (70%) for pediatric mental disorders (Bogdan et al, 2023). The target training duration of 300 minutes was met at 88% for RW and 100% for FB.…”
Section: Discussionmentioning
confidence: 86%
“…Participants achieved an 87% completion rate of the entire research protocol, surpassing the expected rate (70%) for pediatric mental disorders (Bogdan et al, 2023). The target training duration of 300 minutes was met at 88% for RW and 100% for FB.…”
Section: Discussionmentioning
confidence: 86%
“…An important focus of the studies in the special issue is on outcomes and prognosis, such as those demonstrating an association between Attention-Deficit/Hyperactivity Disorder (ADHD) and cardiovascular problems (Li et al, 2023) and sleep problems (Marten et al, 2023), as well as for poor health-related quality of life associated with low socio-economic status amongst children and adolescents with ADHD (Sevastidis et al, 2023). Bogdan et al (2023) presented a comprehensive summary of the main characteristics of longitudinal studies investigating child and adolescent mental health conditions in the general population; Aymerich et al (2023) found that internalising and externalising problems are present in children with enuresis or encopresis; while Pollard et al (2023) observed that anxiety problems during childhood are associated with multifaceted poor outcomes and considerable economic costs.…”
mentioning
confidence: 99%
“…Bogdan et al. ( 2023 ) presented a comprehensive summary of the main characteristics of longitudinal studies investigating child and adolescent mental health conditions in the general population; Aymerich et al. ( 2023 ) found that internalising and externalising problems are present in children with enuresis or encopresis; while Pollard et al.…”
mentioning
confidence: 99%